2022
DOI: 10.1136/bmjresp-2022-001337
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide retrospective observational study of idiopathic dendriform pulmonary ossification: clinical features with a progressive phenotype

Abstract: BackgroundDiffuse pulmonary ossification is a specific lung condition that is accompanied by underlying diseases. However, idiopathic dendriform pulmonary ossification (IDPO) is extremely rare, and the clinical features remain unclear. In this study, we aimed to report the clinical characteristics of IDPO.MethodsWe conducted a nationwide survey of patients with IDPO from 2017 to 2019 in Japan and evaluated the clinical, radiological, and histopathological findings of patients diagnosed with IDPO.ResultsTwenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Diffuse pulmonary ossification (DPO) is a rare pulmonary condition characterized by diffuse formation of mature bone in the lungs [ 5 ]. Based on two retrospective autopsy-based studies, the incidence of DPO ranges from 0.16% to 0.4% [ 6 , 11 ] with 80%–88% of cases occurring in men [ 5 , 6 , 11 ]. It is believed that DPO is a clinically under-recognized entity [ 7 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diffuse pulmonary ossification (DPO) is a rare pulmonary condition characterized by diffuse formation of mature bone in the lungs [ 5 ]. Based on two retrospective autopsy-based studies, the incidence of DPO ranges from 0.16% to 0.4% [ 6 , 11 ] with 80%–88% of cases occurring in men [ 5 , 6 , 11 ]. It is believed that DPO is a clinically under-recognized entity [ 7 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary ossification can be subdivided into DPO (i.e., dendriform pulmonary ossification) and nodular pulmonary ossification (NPO) [ [4] , [5] , [6] ]. DPO is characterized by ramifying spicules of mature woven bone arranged in a serpentine fashion along the alveolar septa and is associated with fat or bone marrow elements in most cases [ 7 ]; conversely, NPO has round, and well-circumscribed outlines and is generally devoid of fat and marrow elements [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most of the described cases were asymptomatic, evaluation of clinical course of the disease revealed signs of slow progression [5].…”
mentioning
confidence: 93%
“…An accurate prognosis of DPO is difficult to determine, because of very limited number of cases with long-term follow-up data, but most of the previously published cases were asymptomatic and remained stable for many years [4]. In 2022, Nishioka et al [5] conducted a nationwide survey of patients with idiopathic DPO from 2017 to 2019 in Japan. Authors identified 22 cases of idiopathic DPO and estimated its' prevalence as 0,16 case per million.…”
mentioning
confidence: 99%